Teknik Rebozo terhadap Intensitas Nyeri Kala I Fase Aktif dan Lamanya Persalinan pada Ibu Multigravida - Yulidian Nurpratiwi; Muhammad Hadi; Idriani Idriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine Rebozo Shake The Apples (RSTA) effectiveness and Rebozo Sifting While Lying Down (RSWLD) on the intensity of pain during the first stage of the active phase and the duration of labor in multigravida mothers. This research method is a quasi-experiment with two group pre and post design. This study indicates that there is a difference in the mean intensity of pain in the first stage of active labor in multigravida mothers before and after giving RSTA & RSWLD (p-value = 0.007). Whereas in the length of work, there was no significant difference in the average size of labor between the RSTA and RSWLD technique interventions (p-value = 0.351), and the effectiveness of the two Rebozo techniques had the same variant, meaning they were equally effective in diverting labor pain during the active phase and duration of delivery (p-value = 0.118). In conclusion, they are giving RSTA, and RSWLD can delay labor pain intensity during the first stage of the active phase and the duration of labor in multigravida mothers. Keywords: Pain intensity, duration of labor, Multigravida, Rebozo technique